Horizontal sound localisation accuracy in individuals with conductive hearing loss: effect of the bone conduction implant. (2nd September 2018) - Asp, Filip; Reinfeldt, Sabine
Abstract: Objective: The objective of this study is to quantify the effect of the Bone Conduction Implant (BCI) on sound localisation accuracy in subjects with conductive hearing loss (CHL). Design: The subjects were tested in a horizontal sound localisation task in which localisation responses were objectively obtained by eye-tracking, in a prospective, cross-sectional design. The tests were performed unaided and unilaterally aided. The stimulus used had a spectrum similar to female speech and was presented at 63 and 73 dB SPL. The main outcome measure was the error index (EI), ranging from 0 to 1 (perfect to random performance). Study sample: Eleven subjects (aged 21–75 years, five females) with BCI participated in the study. Their mixed/conductive hearing loss was either unilateral ( n = 5) or bilateral ( n = 6). Results: Three of five subjects (60%) with unilateral CHL, and four of six subjects (67%) with bilateral CHL showed significantly improved sound localisation when using a unilateral BCI ( p < .05). For the subjects with bilateral CHL, a distinct linear relation between aided sound localisation and hearing thresholds in the non-implant ear existed at 73 dB SPL (18% decrease in the EI per 10 dB decrease in pure-tone average, r = 0.98, p < .001). Conclusions: Individuals with mixed/conductive hearing loss may benefit from a unilateral BCI in sound localisation.